PENGARUH PERSEPSI JAMINAN PRODUK DAN KUALITAS INFORMASI TERHADAP KEPERCAYAAN KEPADA PERUSAHAAN DAN IMPLIKASINYA TERHADAP MINAT BELI DI E-COMMERCE (Studi di Bukalapak.com) - Iftikhar, Dala Noor; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2017)
This research was conducted to find out the influence of perceived assurance of product and information quality on trust to the company and its implication on buying interest in e-commerce.This research uses perceived assurance of product and information quality as the independent variables and trust to the company as the intervening variable, and buying interest in e-commerce as the dependent variable. This study uses quantitative methodology with Structural Equation Method (SEM) and uses primer and secondary data, the data analysis by collecting questionnaire respondents. There are 222 respondents in this research.The analysis results of this research showed that the two independent variables are perceived assurance of product (0,336) and information quality (0,365) has a positive and significant relationship to the intervening variable that is trust to the company. The two independent variables also has a positive and significant relationship to the intervening variable that is buying interest in e-commerce, which is perceived assurance of product has 0,336 and information quality has 0,336. Furthermore, trust to the company as an intervening variable (0,316) has a positive and significant relationship to the intervening variable that is buying interest in e-commerce.